Peran Kegiatan Literasi dalam Mendorong Kreatifitas Peserta Didik di SMPN 21 Kota Serang - Adi Pratama; Siti Arista; Anastasya Putri M; Fidya Fariha; M. Adham F (Universitas Palangka Raya, 2025)
The aim of this research is to determine the role of literacy activities in encouraging student creativity at SMPN 21 Serang City. It is hoped that literacy, as an important component in education, can help students improve their critical and creative thinking abilities. At this school, literacy activities such as writing, reading and discussions are carried out with the aim of broadening horizons and improving communication skills. This research was conducted qualitatively through case studies and using observations, interviews and documentation of literacy activities in schools. The results show that literacy activities at SMPN 21 Serang City have a significant influence on increasing student creativity, both in academic and non-academic terms. Students are more creative, complete assignments in innovative ways, and participate actively in learning activities.